Polecenie w administracji publicznej. Wybrane problemy - Świderski, Krzysztof (Studia Prawa Publicznego, 2023)
The article presents selected problems concerning instructions in public administration. First, attention is paid to the official instruction. It is issued in service relationships, which differ from employment relationships. By issuing an official direction, the service superior obliges a subordinate employee to perform a specific official activity, including to submit a declaration of knowledge on public issues. An official direction is an individual administrative act. These official instructions are issued when it is necessary to correct the performance of public tasks by a subordinate employee. The obligation to comply with an official instruction is not absolute. The addressee of the instruction may raise objections and even refuse to execute an unlawful official instruction. Instructions issued by a superior authority to a subordinate authority constitute a separate group. Such an instruction is an internal act. It may concern the method of performing tasks or taking specific actions within the scope of operation of a subordinate authority. Instructions issued between public administration authorities are aimed at adapting activities to the directions of public policy and correcting the manner of performing public tasks. There is no appeal against an instruction issued by a superior authority. These are binding. The last category concerns intervention orders. The intervention order does not result from organizational superiority or official subordination. This is a request addressed to the public administration authority to take action to abolish the danger in emergency situations. Intervention orders are issued in particular in matters of protection of life, public health, property, protection of civil rights, maintenance of public policy.